The Role of Green Innovation in Strengthening the Sustainability Performance of Digital Startups in Indonesia - Lidya Agustine Senduk; Chua Toh Hua; Ihda Nur Fathiyah (Pandawan Sejahtera Indonesia, 2026)
The increasing awareness of environmental sustainability has encouraged many digital startups in Indonesia to adopt green innovation as a strategic approach to achieving long-term business resilience. This study aims to explore the role of green innovation in strengthening the sustainability performance of digital startups in Indonesia. Using a qualitative approach, the research gathers insights from interviews with startup founders and managers who have integrated eco-friendly practices into their business operations. The findings reveal that green innovation not only enhances operational efficiency and reduces environmental impact but also strengthens brand reputation and stakeholder trust. Furthermore, startups that embed sustainability principles into their core business models demonstrate greater adaptability to market changes and long-term competitiveness. This study contributes to the understanding of how environmental responsibility can coexist with business growth in the digital startup ecosystem. The implications highlight the need for policy support, technological collaboration, and education to foster green innovation in Indonesia’s startup landscape.